Characteristics of alcohol dependent patients with increased gamma glutamyl transferase levels - Mırsal, Hasan; Kalyoncu, Ö. Ayhan; Pektaş, Özkan; Genç, Yasin; Öztürk, Özgür; Köroğlu, Gültürk; Tan, Devran; Beyazyürek, Mansur (Journal of Dependence, 2006)
Objective: The major biological factor to determine alcohol use is Gamma Glutamyl Transferase (GGT). GGT level in blood increases during chronic alcohol use. This is related to increase in the production of GGT and/or the leakage of GGT after liver destruction due to chronic alcohol use. In this study, sociodemographic characteristics and laboratory tests in alcohol dependent patients with increased GGT levels (>150 U/L) were investigated. Method: A total of 104 patients meeting DSM-IV criteria for alcohol dependence were enrolled for study. After the sociodemographic and clinical characteristics of patients determined, life-time severity of alcohol dependence was measured by Michigan Alcoholism Screening Test (MATT). Gamma glutamyl transferase (GGT), alanine amine transferase (ALT), aspartate amine transferase (AST), mean corpuscular volume (MCV), total cholesterol, triglyceride, high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL) and uric acid levels in blood were measured at starvation. The patients were divided into two groups in the basis of their GGT levels as those with more than and those with less than 150 mg/dl. For statistical analyses, chi-square and t-student tests were applied. Results: 85 male (%81.7) and 19 female (%18.3) patients were included in the study. Their mean age was 43.84 (sd= 9.42). The rates of those with increased and decreased GGT levels were found to be %30.7 (n=32) and %69.3 (n=72), respectively. The mean age of those with increased GGT levels was also high (42.41 sd=8.62; 47.00 sd=10.42). In these groups, the mean values and statistical results based on their clinical characteristics were found as ; MATT (25.63 ss=4.20; 18.97 ss=3.57 t=8.30 p<0.01), period for alcohol use annually (28.22 ss=9.22; 19.17 ss=9.56; t=4.41 p<0.01), period for having problems annually (mean=13.06 ss=6.38; mean=8.97 ss=4.67 t=4.35 p<0.01)), daily alcohol consumption in quantity (mean=14.69 ss=4.56; mean=11.58 ss=5.08 p<0.01). On the other hand, the mean values and statistical results based on biological determinants were fond as; AST (78.19 ss=49.18; 34.34 ss=25.18 t=6.01 p<0.01); ALT (71.88 ss=54.82; 29.47 16.27 t=6.03 p<0.01); MCV (101.97 ss=2.36; 91.75 ss=2.53 t=19.40 p<0.01); total cholesterol (230.91 ss=94.21; 182.42 ss=40.23 t=3.69 p<0.01). For all of these variables, the statistical differences were significant. Conclusion: It was understood that the severity of alcohol dependence was effective on blood GGT level. For this reason, MATT may be used to estimate biological damages caused by alcohol use. In addition, AST, ALT, MCV and total cholesterol levels may also be used for the same purpose because these increase concurrently with GGT.